Insights into the evolution of the new variant rabbit haemorrhagic disease virus (GI.2) and the identification of novel recombinant strains. Issue 4 (11th February 2018) - Silvério, D.; Lopes, A. M.; Melo‐Ferreira, J.; Magalhães, M. J.; Monterroso, P.; Serronha, A.; Maio, E.; Alves, P. C.; Esteves, P. J.; Abrantes, J.
Summary: Rabbit haemorrhagic disease (RHD) is a viral disease that affects the European rabbit. RHD was detected in 1984 in China and rapidly disseminated worldwide causing a severe decline in wild rabbit populations. The aetiological agent, rabbit haemorrhagic disease virus (RHDV), is an RNA virus of the family Caliciviridae, genus Lagovirus . Pathogenic (G1‐G6 or variants GI.1a‐GI.1d) and non‐pathogenic strains (GI.4) have been characterized. In 2010, a new variant of RHDV, RHDV2/RHDVb/GI.2, was detected in France. GI.2 arrived to the Iberian Peninsula in 2011, and several recombination events were reported. Here, we sequenced full genomes of 19 samples collected in Portugal between 2014 and 2016. New GI.2 recombinant strains were detected, including triple recombinants. These recombinants possess a non‐structural protein p16 related to a non‐pathogenic strain. Evolutionary analyses were conducted on GI.2 VP60 sequences. Estimated time to the most recent common ancestor (tMRCA) suggests an emergence of GI.2 in July 2008, not distant from its first detection in 2010. This is the first study on GI.2 evolution and highlights the need of continued monitoring and characterization of complete genome sequences when studying lagoviruses' evolution.